Correction: Kumar et al. Fostering Green Finance for Sustainable Development: A Focus on Textile and Leather Small Medium Enterprises in Pakistan. Sustainability 2022, 14, 11908 - Kumar, Love; Nadeem, Farah; Sloan, Maggie; Restle-Steinert, Jonas; Deitch, Matthew J.; Ali Naqvi, Sohail; Kumar, Avinash; Sassanelli, Claudio (Sustainability, 2025)
There were two errors in the original publication [...]